Primary sclerosing cholangitis. Intubation transhepatic bile duct - Praderi, Raúl; Estefan, Alberto; Zito, Milton; Sarroca, Carlos; Puig, Roberto; Santero, Ernesto; Chiossoni, Marta; de Stefanis, Eduardo (Cirugía del Uruguay, 1973)
The authors relate the first two oases found in Uruguay of primary sclerosing cholangitis proved histologically, and complying with characteristics set in literature for this disease. One of the patients was treated by simple drainage of common bile duct and the other by transhepatic intubation of the bile duct through an old permeable choledocoduodenostomy. We do not believe that transhepatic intubati'On techniques ever been used in treatment of this disease. In this particular case a transhepatic, transgastric tube in seton was placed, so that it could later be changerl